UPAYA MENINGKATKAN KOMPETENSI PENYUSUNAN RPP MELALUI KEGIATAN IN HOUSE TRAINING BAGI GURU SDN 048 SUNGAI BENGKAL BARAT - ALI AMIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This study aims to: 1) To find out the steps for implementing IHT activities in preparing RPP to improve teacher professional competence for teachers at SDN 3 Sungai Bengkal Barat, Tebo Regency in carrying out learning. 2) To find out the improvement of teacher competence at SDN 3 Sungai Bengkal Barat, Tebo Regency, Jambi Province in Developing Learning Implementation Plans through IHT activities. The subjects of this study were all teachers of SDN 3 Sungai Bengka Barat, Tebo Regency, Jambi Province. This research is School Action Research (PTS) which consists of two cycles, each cycle includes the stages of planning, implementation, observation, and reflection. The data analysis technique used is comparative descriptive. From the results of the study it can be concluded that: 1) The steps for implementing IHT in order to improve the professional competence of teachers in preparing lesson plans at SDN 3 Sungai Bengka Barat are as follows: (a) Delivering announcements to teachers about the implementation of IHT activities regarding the preparation of lesson plans; (b) Prepare guidance materials in the form of implementation of learning accompanied by simulations; (c) Preparing IHT instruments; (d) Carry out IHT activities without interfering with learning activities; and e) Carrying out observations in the classroom when learning activities are carried out by the teacher; and 2) IHT can improve the professional competence of SDN 3 Sungai Bengkal Barat teachers in preparing lesson plans. This is indicated by the increasing professional competence of teachers both in the preparation and implementation stages. This is indicated by the increase in competency achievement from 69.58 in the initial condition, to 72.81 at the end of Cycle 1 action, and increased to 83.13 in Cycle II action. ABSTRAKPenelitian ini bertujuan untuk: 1) Untuk mengetahui langkah-langkah pelaksanaan kegiatan IHT dalam menyusun RPP untuk meningkatkan kompetensi profesional guru bagi guru di SDN 3 Sungai Bengkal Barat, Kabupaten Tebo dalam melaksanakan pembelajaran. 2) Untuk mengetahui peningkatan kompetensi guru di SDN 3 Sungai Bengkal Barat, Kabupaten Tebo Provinsi Jambi dalam Menyusun Rencana Pelaksanaan Pembelajaran melalui kegiatan IHT. Subyek penelitian ini adalah semua guru SDN 3 Sungai Bengka Barat, Kabupaten Tebo Provinsi Jambi. Penelitian ini adalah Penelitian Tindakan Sekolah (PTS) yang terdiri dari dua siklus, setiap siklusnya meliputi tahap perencanaan, pelaksanaan, observasi, dan refleksi. Teknik analisis data yang digunakan adalah deskriptif komparatif. Dari hasil penelitian dapat disimpulkan bahwa: 1) Langkah-langkah pelaksanaan IHT guna meningkatkan kompetensi profesional guru dalam Menyusun RPP di SDN 3 Sungai Bengka Barat adalah sebagai berikut: (a) Menyampaikan pengumuman kepada guru tentang akan dilaksanakannya kegiatan IHT mengenai penyusunan RPP; (b) Mempersiapkan materi bimbingan berupa pelaksanaan pembelajaran disertai simulasinya; (c) Mempersiapkan instrumen IHT; (d) Melaksanakan kegiatan IHT dengan tidak mengganggu kegiatan pembelajaran; dan e) Melaksanakan pengamatan di kelas saat dilaksanakan kegiatan pembelajaran oleh guru; dan 2) IHT dapat meningkatkan kompetensi profesional guru SDN 3 Sungai Bengkal Barat dalam menyusun RPP. Hal ini ditunjukkan dengan meningkatnya kompetensi profesional guru baik dalam tahap persiapan maupun pelaksanaan. Hal ini ditunjukkan dengan meningkatnya ketercapaian kompetensi dari sebesar 69,58 pada kondisi awal, menjadi sebesar 72,81 pada akhir tindakan Siklus 1, dan meningkat menjadi 83,13 pada tindakan Siklus II.